STAGES OF FORMATION AND IMPLEMENTATION OF STRATEGIES FOR ENSURING ECONOMIC SECURITY OF THE ENTERPRISE (Development Service Industry Management, 2023)
The article presents the essence of the concept of "strategy for ensuring the economic security of enterprise," in particular, it is defined that this concept is understood as a set of actions and decisions taken and implemented by the enterprise to ensure its own economic security. Economic safety management is implemented at various levels of strategic management in particular: operational, which focuses on short-term or daily issues related to production activities and the organization's ability to withstand or adapt to threats; tactical, which focuses on short and med-term planning, assessment of the ability of the enterprise to adapt; strategic, which focuses on the long term.The formation and implementation of the strategy for ensuring the economic security of the enterprise consist of a sequence of stages: 1) analysis of the environment of the enterprise, including the collection and analysis of information of the external and internal environment of the enterprise; 2) defining the goals of ensuring economic security of the enterprise, including the formulation of specific goals; 3) analysis of alternatives and the formation of a strategy for ensuring the economic security of the enterprise, which is related to the consideration of alternatives and strategies to achieve the set goals; 4) implementation of a strategy for ensuring economic security of the enterprise through the development of actions for chosen strategy implementation; 5) comparing the achieved results and set goals to assess and monitor the current strategy for ensuring economic security of the enterprise. The analysis of each of these stages was done. The toolkit used in accordance with the stages of formation and implementation of the strategy for ensuring the economic security of the enterprise, in particular, using: at stage 1 – SWOT analysis, PESTLE - analysis, analysis of the competitive environment (Porter's Five Forces), analysis of strategic groups, formation of the profiles of customers, competitors and suppliers; at stage 2 – SMART criteria, key performance indicators (KPI), management by objectives (MBO), balanced scorecard (BSC), objectives and key results (OKR); at stage 3-5: POSIES model, Gap analysis, Benefit-cost analyzis (BCA), Decision Matrix, Weighted Scoring Model, Risk and Opportunity Analysis, Hoshin Kanri Matrix.
Keywords: strategy; economic security strategy; economic security management; strategy formation; strategy implementation tools